2019
DOI: 10.18870/hlrc.v9i1.435
|View full text |Cite
|
Sign up to set email alerts
|

Predicting education science students’ statistics anxiety: The role of prior experiences within a framework of domain-specific motivation constructs

Abstract: Based on a cognitive-motivational modeling of construct relations, the present study aimed at analyzing the role of prior statistics experiences to ex­­plain education science students’ statistics anxiety. Data were analyzed from two independent samples which consisted of N = 113 and N = 87 participants – using a different operationalization of the experience variable in each case. In both samples, analyses demonstrated students’ statistics anxiety to be substantially ex­plained by their self-concept and negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…Further, according to Chew and Dillon (2014b) anxiety towards statistics consists of: (Baloğlu, 2003;Chew & Dillon, 2014a;Dykeman, 2011;Faber & Drexler, 2020;Paechter et al, 2017;Pan & Tang, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Further, according to Chew and Dillon (2014b) anxiety towards statistics consists of: (Baloğlu, 2003;Chew & Dillon, 2014a;Dykeman, 2011;Faber & Drexler, 2020;Paechter et al, 2017;Pan & Tang, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A belief that research skills are required only in academic filed and not required in other fields is another factor leading to development of negative attitude towards statistics and research skill. In a recently published paper, authors found that many students from social science stream do not perceive statistical skills useful in their career [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, motivation is a substantial factor in conditioning anxiety (Luo et al 2020 ). For example, students having low mathematical proficiency will display higher anxiety rates (Faber and Drexler 2019 ) and negative attitudes towards statistics (Bromage et al 2021 ). According to Self-Determination Theory (SDT) by Deci and Ryan ( 2008 ), motivation can either be intrinsic or extrinsic.…”
Section: Motivational Orientationmentioning
confidence: 99%